PENINGKATAN HASIL BELAJAR PERPAJAKAN MELALUI MEDIA TAXI SNADERS PADA SISWA XI B SMK PL TARCISIUS 2 (Dinamika Pendidikan, 2012)
Vocational School (SMK) is an educational institution to transfer knowledge about the tax. Unluckily, teaching learning process in delivering this material was monotonous, so it needed a medium called TAXI SNADERS. The objective of the study was to increase interest and learning outcomes taxation on Value Added Tax (VAT) and Sales of Luxury through a medium called TAXI SNADERS. The result of the study showed that there was improvement toward students’ interest for 14.5%. On the 1st cycle, students’ interest was only 67.25%, then it increased up to 81.75% on the 2nd cycle. Moreover, students’ learning outcomes also increased for 20% in post test. It was 67% on the 1st cycle and rose to 87% on the 2nd cycle.